2016
DOI: 10.1016/j.bbapap.2016.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the CupB6 adhesive tip from the chaperone-usher family of pili from Pseudomonas aeruginosa

Abstract: Pseudomonas aeruginosa is a Gram-negative opportunistic bacterial pathogen that can cause chronic infection of the lungs of cystic fibrosis patients. Chaperone-usher systems in P. aeruginosa are known to translocate and assemble adhesive pili on the bacterial surface and contribute to biofilm formation within the host. Here, we report the crystal structure of the tip adhesion subunit CupB6 from the cupB1–6 gene cluster. The tip domain is connected to the pilus via the N-terminal donor strand from the main pilu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Pseudomonas aeruginosa is the most frequent gram‐negative bacterium associated with nosocomial and life‐threatening chronic infections (Rasheed et al., ). Oxygen is vital for such organism due to its absolutely aerobic nature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pseudomonas aeruginosa is the most frequent gram‐negative bacterium associated with nosocomial and life‐threatening chronic infections (Rasheed et al., ). Oxygen is vital for such organism due to its absolutely aerobic nature.…”
Section: Resultsmentioning
confidence: 99%
“…So, it can prevent the growth of absolute aerobic bacteria depending on its concentration in coatings or films. Regarding the relationship between P. aeruginosa and edible films, it should be mentioned that P. aeruginosa is often used as a model organism for the study of biofilms (Rasheed et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…Phyre2, a sequence/structure comparison tool [ 34 ], revealed that there are distinct adhesins present in the UshC and YraJ subgroups. While some are more similar to the LpfD adhesin [ 35 ], others are more similar to the Pseudomonas adhesin CupB6 ([ 36 ]; figure 4 b ; electronic supplementary material, table S5). This dichotomy is further reflected in the chaperones that assemble the adhesin subunits (electronic supplementary material, figure S2), which cluster similarly to the phylogenetic history of the usher proteins, largely consistent with an LGT event acting upon the entire chaperone–usher operon, although the ordering of the inner branches is not stable with low support values.…”
Section: Resultsmentioning
confidence: 99%
“…Part of the chaperone-usher system in P. aeruginosa , known to assemble pili on the bacterial surface, the fimbrial subunit CupB6 (Target 37) of P. aeruginosa is the tip adhesion subunit that is attached to the main pilin shaft. The surface-exposed polyproline helix of CupB6 is part of the adhesion domain, and is believed to mediate a range of protein-protein interactions (Rasheed et al, 2016). In S. aureus , Target ID 37 or ‘biofilm-associated surface protein’, mediates intercellular adhesion and biofilm formation, with the N-terminal lobe of the protein identified to have a significant role (Ma et al, 2021).…”
Section: Resultsmentioning
confidence: 99%